2019
DOI: 10.4322/2526-8910.ctoao1869
|View full text |Cite
|
Sign up to set email alerts
|

O uso de jogos interativos por crianças com síndrome de Down

Abstract: Introduction: Playing is fundamental for children's development and an important resource in working with children, but it is important to consider that toys and games have been transformed and the virtual games were included, which started to be used in Occupational Therapy. Objective: To analyze three platforms and six virtual games, to describe the participation of children with Down syndrome in the use of interactive games and to identify the most accessible platform, and the preference of the children. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…A virtual labyrinth task using a cell phone (n o 10) was also used to verify the development over time of acquisition and retention skills in children with DS in aspects related to motor learning, realizing that, despite performing the tasks, the children with DS need more time than the other children to complete the maze [ 58 ]. Platforms were also tested in a study comparing six interactive games from Leap Motion, Nintendo platforms Wii ® and Timocco, investigating which aspects of the games were of more benefit, with aspects such as easiness and fun being the most relevant for DS children [ 59 ]. The computer virtual maze task was used in another study (n o 13), where the researchers found that individuals with DS had ease of acquiring and retaining information, but had difficulty transferring the task presented on the computer to a real situation [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…A virtual labyrinth task using a cell phone (n o 10) was also used to verify the development over time of acquisition and retention skills in children with DS in aspects related to motor learning, realizing that, despite performing the tasks, the children with DS need more time than the other children to complete the maze [ 58 ]. Platforms were also tested in a study comparing six interactive games from Leap Motion, Nintendo platforms Wii ® and Timocco, investigating which aspects of the games were of more benefit, with aspects such as easiness and fun being the most relevant for DS children [ 59 ]. The computer virtual maze task was used in another study (n o 13), where the researchers found that individuals with DS had ease of acquiring and retaining information, but had difficulty transferring the task presented on the computer to a real situation [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Los autores recogen datos con un protocolo de análisis de juegos, un guion de evaluación de la experiencia del usuario, un tablero de comunicación y la grabación de los juegos en video. Concluyen, al margen de ciertas dificultades de desempeño asociadas a las características de una discapacidad intelectual y sin entrar en pormenores de cada una de ellas, que se produce una correlación entre el rendimiento obtenido en el juego y el interés mostrado y la preferencia de elección refiere conciencia de diversión (Pelosi et al, 2019).…”
Section: Rendimiento Y Mejora Del Alumnadounclassified